Concrete-concrete shear friction behavior under cyclic loading: Laboratory test, mathematical modeling, and code provisions. (November 2022) - Leblouba, Moussa; Taklas, Mohamad; Barakat, Samer
Abstract: An experimental program was executed to investigate the concrete-concrete dry friction behavior considering different surface roughness conditions, test rates, and normal stresses. Based on this, we present the mathematical modeling of the friction hysteresis behavior and assess the accuracy of reinforced concrete design codes. The mathematical friction models include the LuGre and Dahl models. The parameters of each model were identified using a hybrid global optimization algorithm (particle swarm optimization) and a local optimizer. All model parameters were calibrated and related to testing variables, such as average roughness, test rate, and additional normal stress. Design codes considered in the present paper include AASHTO LRFD, ACI 318, and Eurocode 2 (EN 1992-1-1). Comparing the test results and mathematical models showed that both the Dahl and LuGre models could replicate the shear friction hysteretic behavior. However, the LuGre model was superior in capturing more realistic features, such as the breakaway and velocity effects. The test results and code provisions showed that the AASHTO LRFD and ACI 318 predictions are conservative for smooth surfaces and less conservative for rough surfaces. EN 1992-1-1, on the other hand, was less conservative for all surface roughness types.